O descompasso de uma experiência: avaliação do Programa Habitar Brasil na Comunidade África-Natal/RN - Arimateia, Emmanuela Wanderly Campos (2007)
This research deals with the evaluation of the Programa do Governo Federal para Urbanização de Favelas Habitar Brasil(1993) carried out in the Africa slum - Redinha neighbourhood in Natal-Rn. This study carried out in period from 2005 to 2006 searches to identify the effects of the actions proposed by Program in 1993-1994 about the current urbanistic configuration of the Africa community. It analyzes the effectiveness in the process of achievement of the considered objectives to habitation, communitity equipments, infrastructure and agrarian regularization. On the evaluation process, it has been as reference the works developed by Adauto Cardoso (2004), Blaine Worthen (2004), Ronaldo Garcia (2001) and Rosângela Paz (2006). About the Habitational Policy with approach to the Urbanistic Right and the right to the housing, the reflections by Raquel Rolnik, Nabil Bonduki, Ermínia Maricato, Saule Júnior, Betânia de Moraes Alfonsin and Edésio Fernandes are main references. To gauge the execution of the objectives proposed by Habitar Brasil in 1993, it has searched in the documentary data of the time and in information gotten in interviews with technicians that had participated of the program, consistent references on what was considered, what was executed and the process of the intervention of Habitar Brasil in the Africa community. The area analysis in 2005-2006 has developed on the base of the urbanistic survey of the current situation from the four performance lines of the Program: habitation, infrastructure, community equipments and agrarian regularization, with a current urbanistic evaluation of Africa considering the intervention carried out in 1993 and 1994. The study points out the context of Brazilian Habitational Policy where the Programa Habitar Brasil was launched, explaining the main principles of the Program. In terms of local, it empahsizes the administrative-political factors that had contributed so that Natal-Rn city has been pioneering in the resources captation of Habitar Brazil (1993). Considering Habitar Brazil in Africa, the work argues and presents the intervention diagnosis and the proposal, developed by Program in 1993 evidencing the local problem of the time. After that, it makes a current reading of the area, identifying in 2006 representative elements of Habitar Brasil (1993-1994) for the Africa community. It identifies significant advances in the constitution of the institucional apparatus of the plaining system of Habitation of Social Interest for the city of Natal and points the fragilities in the implementation of the urban infrastructure actions and above all in the achievement of the objectives of the agrarian regularization